2019
DOI: 10.1007/s11357-019-00118-7
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β promotes basement membrane fibrosis, alters perivascular cerebrospinal fluid distribution, and worsens neurological recovery in the aged brain after stroke

Abstract: Aging and stroke alter the composition of the basement membrane and reduce the perivascular distribution of cerebrospinal fluid and solutes, which may contribute to poor functional recovery in elderly patients. Following stroke, TGF-β induces astrocyte activation and subsequent glial scar development. This is dysregulated with aging and could lead to chronic, detrimental changes within the basement membrane. We hypothesized that TGF-β induces basement membrane fibrosis after stroke, leading to impaired perivas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 48 publications
(85 reference statements)
1
31
0
Order By: Relevance
“…Overexpression of TGF‐β in astrocytes develops Alzheimer's like pathology by impairing the brain microvasculature and thickens the basement membrane, 52‐54 which suggests deposition of amyloid‐β peptide. A similar role of TGF‐β has also been confirmed after stroke 55 . Here we provided evidence that overexpression of let‐7i in ECs after stroke reduced collagen around vessel.…”
Section: Discussionsupporting
confidence: 82%
“…Overexpression of TGF‐β in astrocytes develops Alzheimer's like pathology by impairing the brain microvasculature and thickens the basement membrane, 52‐54 which suggests deposition of amyloid‐β peptide. A similar role of TGF‐β has also been confirmed after stroke 55 . Here we provided evidence that overexpression of let‐7i in ECs after stroke reduced collagen around vessel.…”
Section: Discussionsupporting
confidence: 82%
“…Speaking of neurogenesis, it is inevitable to refer to GSK-3β, inhibition of which increases the proliferation of neural progenitors and promotes neurogenesis in some research 18 – 20 . Pro-differentiation factors such as Wnt and pro-proliferation factors secreted by astrocytes can also stimulate neurogenesis 21 . Therefore, whether IL-17 plays a negative role on neurogenesis by regulating cell proliferation and inflammation after stroke and the exact mechanism underlying is still not determined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, matrix adhesion by endothelial β1-integrin receptors affect claudin-5 expression and regulate BBB permeability (Osada et al, 2011). Interestingly, studies have also indicated the importance of the basement membrane in cerebrospinal fluid regulation (Morris et al, 2016;Albargothy et al, 2018;Howe et al, 2019). Impaired basement membrane integrity is a significant contributor to neuronal loss after stroke.…”
Section: Effects Of Stroke On the Basement Membranementioning
confidence: 99%
“…Aging is also an important factor in basement membrane integrity after stroke. TGF-β signaling in hypoxic astrocytes induces basement membrane fibrosis and chronically impairs perivascular CSF distribution, specifically in aged animals after permanent MCAo (Howe et al, 2019), providing a new mechanism by which brain injury can lead to prolonged functional impairment in the elderly.…”
Section: Effects Of Stroke On the Basement Membranementioning
confidence: 99%
See 1 more Smart Citation